Integrated effects of silicon supply and water availability on the growth of contrasting common bean genotypes regarding water deficit tolerance: evaluation of root system, gas exchange, water use efficiency, and carbon isotope discrimination ( 13C %0 ) - Carr, Natalia Fernandes (2023)
This study investigated the role of silicon as a mitigator of water stress in two distinct genotypes of common bean (Phaseolus vulgaris L.) plants, BAT 477 and IAC carioca 80SH, known respectively as tolerant and susceptible to water deficit stress. Water stress is a significant constraint in agriculture, impacting crop productivity and yield. Silicon has been reported to enhance plant tolerance to various abiotic stresses, including water deficit. However, its effectiveness in non-accumulator plants, such as common bean, remains unclear. To clarify the role of silicon in non-accumulator plants, three studies were conducted. To achieve this goal, the objectives were to evaluate the uptake and kinetics parameters of silicon by common beans and to determine the impact of silicon on water use efficiency and physiological responses of the plants under water stress conditions. The methodology involved assessing silicon uptake through kinetic parameters such as Imax, Km, and Cmin, as well as analyzing the accumulation pattern of silicon during several phenological stages of the genotypes analyzed. The susceptible genotype had higher Si levels and Si accumulation in plants, most of this element was allocated in the leaves, also, showed an increase in dry plant mass. The tolerant genotype did not accumulate more Si compared to the susceptible genotype. Furthermore, water use efficiency was analyzed through physiological parameters related to gas exchange, relative water content, and carbon isotope discrimination (13C ), serving as indicators of physiological responses to water stress. The findings of this research contributed to a better understanding of the role of silicon in mitigating water stress in common bean, a non-accumulator plant. However, this study also revealed the need for further extensive foundational research and field studies to assess and test the behavior of silicon in different scenarios, with a particular focus on non-accumulator plants, which have received less attention in previous studies